Kinerja Keuangan Menggunakan Du Pont System dan Economic Value Added PT Matahari Department Store Tbk - Syania Nur Azizah; Djoni Djatnika; Radia Purbayati (Indonesian Journal of Economics and Management, 2021)
This purpose of this research is to find financial performance using the approach of Du Pont System and Economic Value Added (EVA) in PT Matahari Department Store Tbk for the period 20142018. The method for this research is a descriptive quantitative with use a secunder data from financial statement obtained from the IDX website. The result that PT Matahari Departmet Store Tbk in the approach of Du Pont System, the calculation of ROA and ROE for 2014-2018 there is a fluctueates tends to decrease. ROA 2018 was decline the industry standard average but ROE was above the industry standard average. In the EVA analysis, PT Matahari Department Store Tbk for five period obtained a positive value, even though in 2017 and 2018 the EVA’s values is descreased. The condition show that while ROA 2018 was decline the industry standard, the company profit generated can provide economic added value to the company.